'﻿Test-tube' evolution wins Chemistry Nobel Prize. (11th October 2018) - Gibney, Elizabeth; Van Noorden, Richard; Ledford, Heidi; Castelvecchi, Davide; Warren, Matthew
Frances Arnold, Gregory Winter and George Smith controlled evolution in the lab to produce greener technologies and new medicines. Frances Arnold, Gregory Winter and George Smith controlled evolution in the lab to produce greener technologies and new medicines. L-R: Gregory Winters, Frances Arnold, George P. Smith